2020
DOI: 10.1111/crj.13238
|View full text |Cite
|
Sign up to set email alerts
|

Serum biomarkers in patients with stable and exacerbated COPD‐bronchiectasis overlap syndrome

Abstract: Introduction Bronchiectasis (B), commonly seen in patients with chronic obstructive pulmonary disease (COPD), is associated with exacerbations and predicts mortality. Objectives To differentiate patient groups with COPD‐(B+) or COPD‐(B−) and their exacerbations by using inflammatory markers. Methods Consecutive COPD patients were divided into two groups according to findings on high resolution thorax CT (HRCT) images using Smith and modified Reiff scores. Patients were prospectively followed for possible futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…As result of chronic bronchial infection and consequent inflammation in both COPD and bronchiectasis, serum levels of inflammatory biomarkers, such as IL-6, IL-8 and CRP are increased in BCO patients [80]. Also, Nigro et al showed that in BCO patients, the levels of inflammatory cytokines such as IL-2, IL-4, IL-8, IFN-γ, and GM-CSF were significantly higher, while IL-10 expression levels were lower than those of the control group.…”
Section: Copd and Bronchiectasismentioning
confidence: 99%
“…As result of chronic bronchial infection and consequent inflammation in both COPD and bronchiectasis, serum levels of inflammatory biomarkers, such as IL-6, IL-8 and CRP are increased in BCO patients [80]. Also, Nigro et al showed that in BCO patients, the levels of inflammatory cytokines such as IL-2, IL-4, IL-8, IFN-γ, and GM-CSF were significantly higher, while IL-10 expression levels were lower than those of the control group.…”
Section: Copd and Bronchiectasismentioning
confidence: 99%